STATUS AND ROLE FEATURES OF PRESIDENT INSTITUTION IN FRAMES OF POWER MARKET - Мовчан, У.І.; Работягова, І.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article studies some special role features of president institution in semi-presidential systems, the actual degree of president engagement into the national power market, analyses the world experience of premier-president powers division, gives the recommendations to power balance achievement in Ukraine.